Knowledge, attitudes, and practise toward cancer genetic testing among healthcare workers in the oncology clinic at Sultan Qaboos Comprehensive Cancer and Research Center (SQCCCRC) - Al, Malki Suad (Department of Pathology, 2025)
The incidence of cancer is rising and has emerged as a significant public health challenge in Oman. Approximately 5-10% of all cancer cases are attributed to high penetrance genes, which account for inherited forms of cancer. Due to the shortage of genetic counsellors and medical geneticists in Oman, there is a need to involve other healthcare workers in oncology clinics in the genetic testing process. As there is no prior research on healthcare worker readiness to conduct these services, this study aimed to assess their knowledge, attitudes, and practices regarding germline cancer genetic testing. METHODOLOGY: A quantitative study design, in which an online structured questionnaire was distributed among medical specialists, medical officers and clinical nurse specialists working in the oncology clinic at the Sultan Qaboos Comprehensive Cancer Care and Research Centre (SQCCCRC). The data were analysed using descriptive statistics. Fisher's exact tests and univariable binary logistic regression models were used to identify factors associated with the use of cancer genetic testing and factors related to participants' attitudes. RESULTS: 83 oncology healthcare workers participated representing a response rate of 69.1%. Knowledge: Participants demonstrated low to moderate knowledge of key concepts of hereditary cancer. Specialists showed moderate knowledge, with a mean score of 2.58 (SD ±1.36), while both Clinical Nurse Specialists (CNS) and medical officers reported lower, identical scores of 1.80 (SD ±1.28 and SD ±1.26, respectively) out of 5. Attitude: Only 17% considered themselves competent or confident in providing genetic counselling, including nine specialists and five medical officers, while none of the CNS felt competent, and only 4% felt very well qualified to recommend genetic testing. The majority of respondents expressed positive attitudes towards the availability of guidelines and access to genetic testing services. Additionally, 57.83% of respondents demonstrated positive attitudes toward clinical utility, while 38% and 78% expressed concerns about confidentiality and medical insurance discrimination, respectively. Furthermore, 70% expressed interest in receiving continuous medical education related to cancer genetics. Practices: 64% of participants reported referring patients for genetic testing, and 53% indicated that they assess whether their patients are candidates for genetic testing. Despite this, only 24 (29%) of the participants reported directly ordering genetic tests. While most participants actively collect medical and first-degree relatives' family histories, significant gaps remain, particularly in documenting information about second-degree relatives (SDR) and the age of cancer diagnoses in relatives. Patients' interest in genetic testing was notable, and participants reported expectations that they would increase their direct involvement in ordering genetic tests over the next five years. CONCLUSION: The findings reveal clear gaps in the knowledge required for effective first-line genetic counselling and testing. Findings also emphasize the critical role of targeted cancer genetics training and institutional support in ensuring that healthcare providers are adequately prepared and confident to deliver pre-test genetic counselling to their patients